2018
DOI: 10.1097/sap.0000000000001332
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of the Medial Femoral Condyle Flap for Extremity Reconstruction and Identification of Risk Factors for Nonunion, Delayed Time to Union, and Complications

Abstract: Extremity reconstruction using the MFC corticocancellous flap results in a high rate of union yet minimal donor morbidity for a challenging patient cohort. Previous surgery was a risk factor for increased time to union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A recent study showed that previous surgery is a risk factor for nonunion following MFC reconstruction of both the upper and lower extremity. 18 History of prior failed arthrodesis as a risk factor for nonunion after MFC reconstruction likely reflects a higher degree of compromised blood supply to the residual hindfoot bones as a result of the significant prior surgical intervention(s).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that previous surgery is a risk factor for nonunion following MFC reconstruction of both the upper and lower extremity. 18 History of prior failed arthrodesis as a risk factor for nonunion after MFC reconstruction likely reflects a higher degree of compromised blood supply to the residual hindfoot bones as a result of the significant prior surgical intervention(s).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of 29 patients at a single institution, there were no cases of permanent donor site injury such as knee instability, femoral fracture, pain, or numbness. (Kazmers et al, )…”
Section: Discussionmentioning
confidence: 99%
“…(Masden, Iorio, & Higgins, ) The average vascular pedicle length is 7.7 cm. (Kazmers et al, ) When resection is limited to the MFC, knee stability is not affected long‐term and there is very minimal risk of an iatrogenic femur fracture. Additionally, while it is difficult to identify the nutrient vessels for smaller bone segments of other VBGs, the vascular territory of bone perfused by the DGA has been studied, and therefore taking small segments from it are more predictable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations